1954
DOI: 10.1002/hlca.19540370427
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von 6‐Äthyl‐α‐ und 6‐Äthyl‐β‐jonon

Abstract: Z u s a m m e n f a s sung.Aus 1,l-Dimethyl-2-oxymethyl-cyclohexanon-( 3) wird das leicht dimerisierbare 1,l-Dimethyl-2-methylen-cyclohexanon-( 3 ) in Verdunnung hergestellt und mit Acetessigester nach Michuel kondensiert, wobei je nach Versuchsbedingungen ein mono-oder ein bicyclisches Kondensationsprodukt entsteht. Beide ergeben bei der Saurespaltung 1,l-Dimethyl-2-( ~-carboxy-athyl)-3-oxy-3-carboxy-methylcyclohexan. Diese Oxy-dicarhonsaure wird lactonisiert und die erhaltene Lactonsaure der Pyrolyse unterwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1954
1954
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The required enone ( 5 ) was synthesized from methyl 2-ethyl-3-oxobutanoate according to previously described procedures (Scheme S2B). 57 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The required enone ( 5 ) was synthesized from methyl 2-ethyl-3-oxobutanoate according to previously described procedures (Scheme S2B). 57 …”
Section: Resultsmentioning
confidence: 99%
“…The required enone (5) was synthesized from methyl 2-ethyl-3oxobutanoate according to previously described procedures (Scheme S2B). 57 With the necessary building blocks in hand, we attempted the key proline-mediated step for formation of ring D. Initial experiments with crude β-carboline 4 treated with an excess of enone 5 in the presence of proline, afforded the desired ketones in moderate yield as a mixture of epimers 6 and 7. Importantly, we found that the major diastereomer 6 was obtained in high enantiomeric excess (ee), while the minor diastereomer 7 was obtained in much lower ee.…”
Section: Figures S1 S2 and S3mentioning
confidence: 99%
“…A new group of antinicotine substances has been described by Surber (214); they antagonize the effects of nicotine without depressing gang lionic transmission or the response to other "nicotine-like" substances, such as dimethylphenylpiperazine. Their mode of action is not yet known.…”
Section: Ganglion -Blocking Substancesmentioning
confidence: 99%